2016
DOI: 10.15173/glj.v7i1.2545
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Influence of Labor Informality on Subjective Well-Being

Abstract: <p>This paper explores the relationship between informal employment and the subjective well-being of informal employees and self-employed workers in Mexico. The main hypothesis is that labor informality has a significantly negative impact on the level of self-reported life satisfaction and happiness of individuals. This effect is sustained even when controlling for potentially determinant socio-demographic factors, in particular income. The module of self-reported well-being (BIARE) that was part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…The negative impact of informal employment on the subjective well-being of individuals is empirically corroborated by studies in Colombia [ 40 ], Mexico [ 38 ], and Central American countries [ 51 ]. Most notably, Lopez-Ruiz, Artazcoz [ 51 ] used a multidimensional measurement of informal employment, including absence of an employment contract, lack of social security coverage, or employment status, and found that not having social security coverage is the strongest predictor of poor subjective health and mental health for informal workers in both women and men.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The negative impact of informal employment on the subjective well-being of individuals is empirically corroborated by studies in Colombia [ 40 ], Mexico [ 38 ], and Central American countries [ 51 ]. Most notably, Lopez-Ruiz, Artazcoz [ 51 ] used a multidimensional measurement of informal employment, including absence of an employment contract, lack of social security coverage, or employment status, and found that not having social security coverage is the strongest predictor of poor subjective health and mental health for informal workers in both women and men.…”
Section: Resultsmentioning
confidence: 83%
“…Diverse types of informal workers were studied in LMICs, including waste workers [ 16 21 ], trash pickers [ 22 ], clay artisans [ 23 ], taxi drivers [ 24 ], artisanal and small-scale gold miners [ 25 ], informal commerce workers [ 26 ], female beer promoters [ 27 ], domestic workers [ 28 ], informal fisheries [ 29 ], and informal workers in the construction and manufacturing industry [ 30 37 ]. The remaining micro-level studies were conducted in LMICs [ 38 43 ] and HIC contexts [ 9 ], rather than focusing on a specific type of informal workers, and analyzed survey data or injury reports to examine the difference in health outcomes between workers in informal and formal employment.…”
Section: Resultsmentioning
confidence: 99%
“…The BIARE sample consists of 10,654 people over 18 years old, representing 70.78 million Mexicans. Despite this survey being relatively recent, some studies have used the data provided by the survey (Hernández García and Tomé González ; Temkin ).…”
Section: Methodsmentioning
confidence: 99%
“…The existing literature on welfare of informal workers is mainly concentrated on studies with respect to specific occupations (Blaauw et al, 2013;Markussen et al, 2018) as well as specific problems like financial inclusion and social security (Hu and Stewart, 2009), working conditions (Kantor et al, 2006), skill and productivity (Sanghi and Sensarma, 2014) etc. Studies on informal workers using the concept of subjective well-being have mainly focused on analysing the effect of informality on well-being through comparison between formal and informal workers (Rojas, 2013;Jütting et al, 2007;Temkin, 2016;Cassar, 2010). Outcomes of these studies are not unanimous and often suggest a parallel strong existence of informal economy with its mixed effects on well-being.…”
Section: Well-being Of the Informal Workersmentioning
confidence: 99%